Evaluation of 27 different biochars for potential sequestration of antibiotic residues in food animal production environments. Issue 1 (March 2015) - Mitchell, Shannon M.; Subbiah, Murugan; Ullman, Jeffrey L.; Frear, Craig; Call, Douglas R.
Highlights Biochar prepared at >500 °C sorbed antibiotics better than lower temperature biochar. Ceftiofur sorbed to biochar more than florfenicol. Pinewood biochar prepared at >550 °C sorbed antibiotics in soil–urine–feces slurry.